A Study of Directional Patterns of Ultrasonic Parametric Array - RAKOV, Denis Sergeevich; RAKOV, Aleksandr S.; KUDRYAVTSEV, Andrey N.; KRASNENKO, Nikolay P.; CHURSIN, Yury A.; MURIN, Maksim A. (Archives of Acoustics, 2019)
The paper presents results of numerical calculations and experimental data on the directional pattern of two 38-element parametric arrays composed of ultrasound sources. Two types of antenna arrays are considered, namely with parallel and coaxial connections of ultrasonic transducers (elements). The results of selecting and functional testing of unit elements are described in this paper. It is found that in the coaxial element connection of the antenna array, the level of side lobes is higher than that in the parallel element connection.